ЕЛЕКТРИЧНЕ ПОЛЕ У ЗШИТО-ПОЛІЕТИЛЕНОВІЙ КАБЕЛЬНІЙ ІЗОЛЯЦІЇ З ЕКСЦЕНТРИЧНІСТЮ ТА ДЕФЕКТОМ НАПІВПРОВІДНОГО ЕКРАНА - І.М. Кучерява (Праці Інституту електродинаміки Національної академії наук України)
The study of two-dimensional electric field in cross-linked polyethylene (XLPE) insulation with eccentricity and a protrusion of the insulation into the internal semiconducting screen of high-voltage cable is carried out by computer modeling. The non-uniformity of the distribution and the regularities of the change in the level of the electric field depending on the considered defects are analyzed. The dependence of the maximum electric field strength on insulation concentricity (within the range of 0–0.5) is presented. The need to prevent the eccentricity of the XLPE insulation system and its defects in the production process of power cables is grounded to ensure their high quality and further reliable operation. Ref. 15, fig. 6.